Woven type smart soft composite for soft morphing car spoiler. (1st February 2016) - Han, Min-Woo; Rodrigue, Hugo; Cho, Seunghyun; Song, Sung-Hyuk; Wang, Wei; Chu, Won-Shik; Ahn, Sung-Hoon
Abstract: Morphing structures making use of smart materials are considered to be a promising technology for the amelioration of the aerodynamic performance of land and air vehicles. In particular, soft morphing structures are capable of continuous curvilinear structural deformation upon actuation without discrete sections that generate aerodynamic losses. In this paper, a woven type smart soft composite consisting of shape memory alloy wires and glass fiber-reinforced composite was fabricated and applied to the rear spoiler of a ⅛-scaled radio-controlled car which is capable of actuating either symmetrically or asymmetrically. To verify its aerodynamic performance, wind tunnel experiments were carried out using a stand-alone spoiler under various wind speeds, angles of attack, and actuation modes. First, the results of the symmetric mode of actuation intended for braking conditions are presented. Second, to generate a yawing moment to assist the vehicle in cornering, the asymmetric mode of actuation was tested in an open-circuit blowing-type wind tunnel. Results of the symmetric and asymmetric modes of actuation were then compared with a symmetric airfoil (NACA 0010) with a flap tested under the same conditions. Lastly, the spoiler was mounted on the small-scale car and wind tunnel tests were conducted to determine the potential of augmentation on aerodynamic performance by implementing the soft morphing spoiler.